AI-POWERED PREDICTIVE MAINTENANCE: A TECHNICAL DEEP DIVE INTO MODERN WEBSITE RELIABILITY ENGINEERING - Shailesh Kumar Agrahari, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This comprehensive article examines the transformative role of AI-powered predictive maintenance in modern website reliability engineering. It explores how machine learning algorithms and advanced analytics are revolutionizing traditional maintenance approaches, enabling organizations to anticipate and prevent system failures before they impact end-users. The article provides an in-depth analysis of the technical architecture underlying these systems, including data collection mechanisms, machine learning pipelines, and automated response systems. It investigates the implementation strategies for predictive maintenance, examining both automated response mechanisms and dynamic resource allocation in cloud environments. The article also evaluates the performance impact of these systems on operational efficiency and cost reduction, while addressing critical security considerations in predictive maintenance deployments. Furthermore, it explores emerging trends in self-healing systems and edge computing integration, providing insights into the future evolution of predictive maintenance technologies. The article demonstrates that AI-powered predictive maintenance represents a paradigm shift in website reliability engineering, offering significant improvements in system reliability, operational efficiency, and cost-effectiveness.